Review on Different Vesicular Drug Delivery Systems (VDDSs) and Their Applications - Alenzi, Asma M.; Albalawi, Sana A.; Alghamdi, Shatha G.; Albalawi, Rawan F.; Albalawi, Hadeel S.; Qushawy, Mona (Recent Patents on Nanotechnology, 2023)
Background: Colloidal dispersions, also known as vesicular drug delivery systems (VDDSs), are highly ordered assemblies composed of one or more concentric bilayers formed by the self-assembly of amphiphilic building blocks in the presence of water. Objective: VDDSs are important to target the entrapped drugs at specific sites inside the body, control the drug release, enhance the drug bioavailability, and reduce undesired side effects. Methods: There are different types of VDDSs suitable for the entrapment of both hydrophilic and lipophilic drugs. According to the patent composition, VDDSs are classified into lipid-based and nonlipid- based VDDSs. Results: There are different types of VDDSs which include liposomes, ethosomes, transferosomes, ufasomes, colloidosomes, cubosomes, niosomes, bilosomes, aquasomes, etc. Conclusion: This review article aims to address the different types of VDDSs, their advantages and disadvantages, and their therapeutic applications.
Keywords: colloidal dispersion